SPATIAL FACTORS OF FORMATION OF CONDITIONS OF ECONOMIC DEVELOPMENT IN UKRAINE - Rodchenko, V.B.; Rekun , G.P.; Prus , Yu. I. (The actual problems of regional economy development, 2021)
The purpose of the article is to develop the theoretical foundations and methodical provisions for the parameters’ transformation of the spatial capital management system in the region under the influence of global challenges. After analyzing the works of leading scientists and analytical materials of world research centers, the work highlights the current trends in business structures due to the transformation of the spatial capital management system; features of the impact of changes in the spatial capital management system on the processes of implementation of public administration and human life. Maturity of different industries from the standpoint of the level of digital transformations is investigated. Among the global challenges of the transformation of the properties of space, the authors singled out digitalization, servicing, Industry 4.0, and the decarbonization of the economy. The paper proves that together these challenges change the traditional understanding of the essence of management as a type of management activity, which is manifested in the transition to the concept of developing differentiated individual performance indicators; permanent reduction of polarization between the concepts of mass production and quality of local goods, works, services; transition from the mass market to the changing market of individual or microgroups of buyers, etc. As a result, under the influence of these processes there are new production systems (wikinomics, new network cooperatives), new methods of delivery of goods (virtual fitting, 3D printing, e-books), new property systems (economics of gift and economics of distributed use, free goods / services); new management systems (independent boards of directors, multisteakholderism, lack of hierarchies, collective leadership); new financing systems (crowdfunding and “ethical banking”); new systems of market organization (mechanisms of co-competition).